2018
DOI: 10.17085/apm.2018.13.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Accidental cut of esophageal temperature probe during lobectomy for lung cancer - A case report -

Abstract: Adequate maintenance of body temperature during general anesthesia is necessary for patients' safety. Perioperative thermal disturbance can cause numerous adverse outcomes such as wound infection, coagulopathy, delayed postanesthetic recovery, and prolonged hospitalization [1][2][3]. Core temperature can be accurately monitored at the tympanic membrane, distal esophagus, nasopharynx, and pulmonary artery [4]. Generally, esophageal temperature probe is used because of its reliability [5] and feasibility in prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although there were no ventilation-related problems, the patient's body temperature did not rise above 36.2 C, and tracheal insertion of the temperature probe was recognized through a routinely performed portable chest X-ray examination after surgery. Lee et al 9 and Dabbous et al 10 reported similar cases involving patients who underwent lobectomy. No abnormalities in ventilation or body temperature occurred during surgery, but part of the temperature probe was found in the resected lung, and tracheal insertion of the temperature probe was thus recognized.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although there were no ventilation-related problems, the patient's body temperature did not rise above 36.2 C, and tracheal insertion of the temperature probe was recognized through a routinely performed portable chest X-ray examination after surgery. Lee et al 9 and Dabbous et al 10 reported similar cases involving patients who underwent lobectomy. No abnormalities in ventilation or body temperature occurred during surgery, but part of the temperature probe was found in the resected lung, and tracheal insertion of the temperature probe was thus recognized.…”
Section: Discussionmentioning
confidence: 88%
“…5 Previous case reports have described inadvertent tracheal insertion of esophageal temperature probes during surgeries. [6][7][8][9][10] In two of these case reports, the patients developed abnormal ventilation. 6,7 In another report, the patient maintained normal ventilation but had an abnormally low body temperature measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 , 15 ] Lee et al reported a case wherein a malpositioned esophageal temperature probe in the right intermediate bronchus was accidentally cut during lung lobectomy. [ 28 ] Moreover, esophageal temperature probes cannot be inserted during surgeries that require an intraoral approach or esophageal manipulation. Tracheal temperature monitoring is convenient in such cases as temperature monitoring can be started immediately after intubation, and the insertion of another temperature probe is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the nasopharyngeal temperatures as intraoperative core temperature; the nasopharyngeal temperature is more reliable compared with bladder temperature, because bladder temperature is strongly influenced by urine flow [15,16]. And, the esophageal probe are at risk of misplacement due to relatively long distance from incisor (approximately 40 cm) compared to nasopharyngeal probe [13,[17][18][19]. However, the distance between the upper body blankets to nasopharynx is closer compared with lower body blanket, and it might raise nasopharyngeal temperature more quickly, even though head was not covered with the upper body blanket in our study.…”
Section: Discussionmentioning
confidence: 99%